Iterative interference cancellation based on decoding algorithm of space-time block coding in frequency-selective fading - DONG Tao; YOU Xiao-hu (Tongxin xuebao)
Considering that the orthogonality of STBC in frequency-selective fading will be destroyed by the multiple path interference（MPI）,an iterative interference cancellation based maximum likelihood sequence estimation（MLSE） decoding scheme was proposed for STBC in frequency-selective fading.Meanwhile,the maximum ratio combining（MRC） method was introduced to improve the proposed scheme,and decrease the computational complexity further.These schemes could effectively make up for the decoding deficiency of conventional STBC in frequency-selective fad-ing.They canceled not only the MPI from even terms corresponding to the orthogonality undestroyed by fading,but also the MPI from odd terms corresponding to the orthogonality destroyed by fading;they has superior performance.More-over,they have lower decoding complexity when compared with direct MLSE decoding of the long sequence signal.Thus they implement good decoding performance with low complexity.